Deviant Behavior of Adolescents in the Digital Era from the Perspective of Islamic Education - Arik Febroza; Alwi Mulya; Ade Darmawan; Praja Purnama Nusa; Janu Darmansyah; Perdi Gusti Cahyadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The digital era has reconstructed the social interaction space that offers communication efficiency as well as massive moral challenges, where the penetration of information technology that is not accompanied by spiritual maturity has triggered various digital social pathologies such as cyberbullying, hoaxes, flexing, and addiction to immoral content. This study aims to analyze the phenomenon of deviant behavior in cyberspace through the perspective of Islamic Religious Education (PAI) and formulate a holistic strategy for overcoming it using descriptive qualitative methods with a literature study approach (library research) that synthesizes findings from various recent literature related to education, ethics, and digital sociology. The results of the analysis show that deviant behavior in cyberspace is rooted in an identity crisis, loss of empathy due to digital anonymity (online disinhibition effect), and erosion of adab, so as a fundamental solution, this study offers a